Penerapan Pembelajaran Penemuan Terbimbing untuk Meningkatkan Kemampuan Komunikasi Sains Mahasiswa - Selpa Pertiwi, Fiza Dora; Hidayat, Toni (Papanda Publisher, 2024)
This study is a Classroom Action Research aimed at describing the implementation of guided discovery learning activities to enhance students' scientific communication at UIN Fas Bengkulu. The success of this research involves several aspects. First, during the learning process, the researchers formed groups with diverse composition. Second, the researcher provided opportunities for all students, especially those with low abilities and less active participation, to express ideas, ask questions, provide answers, and respond to other students' views. Third, the researcher allowed students to solve various problems related to the use of concepts about living organisms. The learning was conducted over two cycles, with each cycle consisting of two sessions to explain the learning materials and one session for written tests. Based on the research results, students' scientific communication improved in each cycle. In cycle I, the average score was 70.9, and in cycle II, it increased to 82. Students' participation scores during the learning process also improved, with cycle I scoring 77.04 and cycle II scoring 94.75. Based on these results, it can be concluded that the implementation of guided discovery learning models can enhance students' scientific communication skills.